4 - Declining job security level and workers’ perfomance in selected banks, South Western Nigeria - Aliyu Taofeek Kolawole; Dr. Albert Oludele AJANI; A. L. Adisa (African Sociological Review, 2015)
The study assessed bank workers’ level of job security and also investigated the relationship between job security level and job performance among employees of the banks. The study adopted cross-sectional research design where primary and secondary data were sourced. Primary data were obtained through both quantitative and qualitative techniques of data collection while Secondary data were extracted from Annual Reports of the selected Banks. The sample consisted of 210 bank workers selected for questionnaire administration and 15 workers for In-depth Interviews (IDIs) especially those that have been working with the bank for the past three years. These comprised both permanent and contract workers. Quantitative data were analyzed using descriptive and inferential statistics while qualitative data were analyzed through content analysis. The result showed that majority (58.7%) considered the level of their job security to be low while (41.3%) considered the level of their job security as high across the selected banks. However, bank by bank evaluations of low level of job security did not show any major differences as Stanbic-IBTC Bank reported (51.4%), Wema Bank (70%), and First Bank (51.4%). The findings also showed that workers, regardless of their perception and feelings of job loss reported increase in their performance. Hence, there existed no significant relationship between job security level and performance (χ2 = 0.75; p> 0.05). The paper concluded that declining job security level is inevitable in the banking industry because of reforms in the Nigeria banking sector. However, this did not lower workers’ performance, otherwise performance were enhanced. It then recommended the need for Nigerian banks to employ the required number of workers they are capable of providing for and put an enabling environment for workers to perform.